"Small in size but mighty in force" – The first principle study of the impact of A/D units in A/D-phenyl-π-phenothiazine-π-dicyanovinyl systems on photophysical and optoelectronic properties. (May 2021) - Slodek, Aneta; Zych, Dawid; Kotowicz, Sonia; Szafraniec-Gorol, Grażyna; Zimosz, Sylwia; Schab-Balcerzak, Ewa; Siwy, Mariola; Grzelak, Justyna; Maćkowski, Sebastian
Abstract: A set of N-octylphenothiazine malononitriles (P1–P4 ) containing ( p -methoxyphenyl, p -trifluoromethylphenyl, 3, 5-bis(trifluoromethyl)phenyl, or p -cyanophenyl) substituents connected via acetylene linker were designed and synthesized. The obtained structures, which exhibit A/D-π-D-A architecture, were characterized by NMR and mass spectroscopy, and elemental analyses. Photophysical, thermal, and electrical properties of these novel dyes P1–P4 were comprehensively studied and confronted with theoretical calculations. They exhibit high thermal stability of up to 306–369 °C. Compounds showed an intramolecular charge transfer (ICT) absorption band at about 480 nm and emission band at around 620 nm with quantum yields between 31 and 50% in chloroform solution. Comparison of the solution and thin film photoluminescence (PL) spectra of P1–P4 exhibit a significant red-shift of 40–70 nm in the thin film PL spectrum. Furthermore, the impact of the end-capped groups in P1–P4 on optical and electrochemical properties was investigated in detail with the support of TD/DFT calculations. The diodes based on P1–P4 with configuration ITO/PDOT:PSS/PBK:PBD:compound/Al were constructed and their electroluminescence (EL) spectra were registered. Considering the preliminary EL investigations, the beneficial effect of the presence of p- cyanophenyl as a substituent (P4 ) was demonstrated. Graphical abstract: Image 1 Highlights: New N-octylphenothiazine malononitriles containing diverse substituents connected via acetylene linker were prepared. Photophysical properties of the novel compounds were carefully studied and compared to the theoretical calculations. The influence of the nature of substituents on the photophysical properties of new compounds was discovered. Correlation between the performance of the OLEDs and different character of substituents on compounds was presented. The best performance of OLED devices was achieved for a diode with the compound containing p- cyanophenyl unit.